2017
DOI: 10.1136/bmjopen-2016-014124
|View full text |Cite
|
Sign up to set email alerts
|

Listening to paediatric primary care nurses: a qualitative study of the potential for interprofessional oral health practice in six federally qualified health centres in Massachusetts and Maryland

Abstract: ObjectivesTo explore the opportunities for interprofessional collaboration (IPC) to improve paediatric oral health in federally qualified health centres (FQHCs), to identify challenges to IPC-led integration of oral health prevention into the well-child visit and to suggest strategies to overcome barriers.SampleNurse managers (NMs), nurse practitioners (NPs), paediatric clinical staff and administrators in six FQHCs in two states were interviewed using a semistructured format.DesignGrounded theory research. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…These findings are coherent with those reported by Bernstein et al. (). Nevertheless, the majority of them do not perform routine children's mouth examination and caries prevention measures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are coherent with those reported by Bernstein et al. (). Nevertheless, the majority of them do not perform routine children's mouth examination and caries prevention measures.…”
Section: Discussionsupporting
confidence: 94%
“…That study found that nurses in diverse roles (i.e., nurse managers, nurse practitioners, and registered nurses), understood the importance of integrating oral health prevention into primary care settings but listed several barriers such as lack of electronic medical record systems, time limitation, lack of oral health knowledge, and more. Several of these findings are coherent with our findings and emphasize the limitations which must be overcome in order to implement oral health prevention by nurses (Bernstein et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of untreated dental caries is high in these children and can have an adverse effect on their systemic health and affect their ability to eat, speak, and learn (CDC, 2019; Golinveaux et al, 2013). Despite the availability of public dental insurance for low-income children, families continue to not prioritize or understand the need for preventative oral health visits in young children (Bernstein et al, 2017). Additionally, many barriers to dental care have been reported, including lack of parental knowledge of oral health care in young children, lack of access to pediatric dental care providers, and dental providers not accepting public insurance (Bradbury-Jones et al, 2013; Close et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the oral health benefits of initiatives that involve both medical and dental professions ( Biordi et al 2015 ; Braun and Cusick 2016 ; Clark et al 2016 ). Non-dental primary care health professionals are well positioned to improve access to dental care ( Bernstein et al 2017 ). More initiatives in early oral health screening and referrals, education and intervention for children and their caregivers by non-dental professionals who have access to priority populations may reduce the inequities in oral health.…”
Section: Discussionmentioning
confidence: 99%